Exploring the caregiver's experience in an innovative homebound hematopoietic stem cell transplantation program. Issue 4 (August 2021) - Jenkelowitz, Juliet; Garzon, Margaux Genoff; Lynch, Kathleen; Shuk, Elyse; Feindler, Eva; Landau, Heather; Applebaum, Allison
Abstract: Objective: Home care for hematopoietic stem cell transplants (HSCTs), an alternative to traditional inpatient or outpatient recovery programs, is safe and feasible but may place greater demand on full-time caregivers. The goal of this study was to characterize the experiences of caregivers in a newly piloted homebound HSCT program as a means of identifying unmet needs and ensuring adequate support. Method: A qualitative approach was utilized. Participants created self-recorded video diaries guided by open-ended prompts at designated time points throughout recovery and participated in a single follow-up interview within four weeks post-discharge. Diaries and interviews were transcribed, analyzed, and coded to identify recurrent ideas and themes. Results: Data were collected from 12 caregivers of homebound HSCT patients. Thematic content analysis yielded four themes: facilitators (external support, sense of normalcy, and patient wellness), challenges (difficulties with transplant care instructions, managing the patient's physical and emotional health, and caregiver psychological distress), roles in recovery (caregiving responsibilities), and analysis of homebound experience (positive outcomes and suggestions for improvement). Significance of results: Caregivers perceived the homebound program as offering high-quality medical care in a setting that provided a sense of normalcy, privacy, and greater level of oversight. Unmet needs included lacking preparedness in completing nursing responsibilities and handling caregiver and patient distress. While the homebound program was preferred to routine hospital care, psychotherapeutic support and programming to improve caregiver preparedness in a homebound HSCT recovery program is indicated.